PENYULUHAN TENTANG KETENTUAN NIKAH SORO PADA PERKAWINAN SUKU KAILI DI KABUPATEN DONGGALA - aifan, aifan; Lakuna , Rosnani (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
his service is entitled Counseling on Soro Marriage Provisions forKaili Tribe Marriages in Donggala Regency. The service in the backgroundof the Soso Marriage Procession still causes debate among certaincommunity groups, because many things can happen. Soro marriages mustnot be registered with the local Population and Civil Registry Serviceor at the Office of Religious Affairs in recognition by the state. Thisprocession is only known to the family and community leaders who can betrusted or appointed by the family carrying out the celebration. Withthis mechanism, it can have an impact on the social conditions of societyas well as other legal aspects. Thus, the Service Team as academics musthelp the community find the root of the problems that arise. Of coursethey must be found. For the purpose of knowing the factors that influencethe occurrence of a kasoro marriage in Kaili tribe marriages and thelegal aspects of carrying out a kasoro marriage based on applicableregulations. The method of this activity is the lecture method andquestion and answer method with the delivery of theoretical mainmaterial, where the material is presented by several people aspresenters with the target being the Kola-Kola Village Office, Kec.Central Banawa Donggala Regency.Keywords: Kaili tribe; Marriage; Soro's marriage.